La estética del secreto en una novela de espionaje : La deuxième mort de Ramón Mercader de Jorge Semprún - Kroll, Simon (Acta Hispanica, 2015)
This paper examines a specific characteristic of spy novels, the aesthetics of secrecy, on the example of Jorge Semprún’s La deuxième mort de Ramón Mercader. An important aspect in the creation of an aesthetic of secrecy in the novel in question is the variation of the famous figure of the double. Ramón Mercader, the protagonist of the novel presents an interesting case of this, which will be analysed in the first part of this paper. The second part of the article points out the overruling organisation principle of the novel: the secret. The complex narratological and temporal structure of the novel obeys to the secret, which makes it the major formal principle of this text. The story does not only narrate secrets but the secret as a formal principle creates a text with plenty of voices and a complex temporal structure, contributing to the creation of an aesthetic of secrecy.